2021
DOI: 10.1590/1516-3180.2020.0168.r1.30102020
|View full text |Cite
|
Sign up to set email alerts
|

Neck pain and associated factors in a sample of high school students in the city of Bauru, São Paulo, Brazil: cross-sectional study

Abstract: BACKGROUND: Neck pain is a major public health problem. OBJECTIVE: The aim of the present study was to determine the prevalence of neck pain among high school students and to analyze associations with sociodemographic variables, use of electronic devices, habitual physical activity practices and mental health problems. DESIGN AND SETTING: Cross-sectional epidemiological study on a sample of high school students in the city of Bauru, São Paulo, Brazil. METHOD: Participants were selected through cluster sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…During the study analysis, the participants were school and university students (6 - 25 years old) with either an equal or adjusted male-to-female ratio. Of the included research, two articles were from Brazil 18,19 , two from Portugal 20 ,,21 , two from Thailand 22 , and one study each was from Ethiopia 23 , Jordan 24 , Iran 25 , Shanghai 26 , Kuwait 27 , Turkey 28 , Lebanon 29 , and Taiwan 30 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the study analysis, the participants were school and university students (6 - 25 years old) with either an equal or adjusted male-to-female ratio. Of the included research, two articles were from Brazil 18,19 , two from Portugal 20 ,,21 , two from Thailand 22 , and one study each was from Ethiopia 23 , Jordan 24 , Iran 25 , Shanghai 26 , Kuwait 27 , Turkey 28 , Lebanon 29 , and Taiwan 30 .…”
Section: Resultsmentioning
confidence: 99%
“…During the study analysis, the participants were school and university students (6 -25 years old) with either an equal or adjusted male-to-female ratio. Of the included research, two articles were from Brazil 18,19 , two from Portugal 20,,21 , two from Thailand 22 , and one study each was from Ethiopia 23 , Jordan 24 , Iran 25 18 , with 150 participants. These studies collected data through interviews, questionnaires, singular questions, and scales, but the most prominent of these scales was the Nordic questionnaire or an adapted version of the Nordic Questionnaire.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the use of electronic devices, the way, i.e., the posture of working on the computer, cell phone, or tablet, is also important. Previous studies have concluded that the sitting position when using a cell phone is a direct risk factor for neck pain (7). Excessive use of electronic devices while studying and reading can lead to the onset of depression symptoms in students.…”
Section: Introductionmentioning
confidence: 99%